Effects of curcuminoids on inflammatory status in patients with non-alcoholic fatty liver disease: A randomized controlled trial. (March 2020) - Saberi-Karimian, Maryam; Keshvari, Mahtab; Ghayour-Mobarhan, Majid; Salehizadeh, Leila; Rahmani, Sepideh; Behnam, Behzad; Jamialahmadi, Tannaz; Asgary, Sedigheh; Sahebkar, Amirhossein
Highlights: Nonalcoholic fatty liver diseases (NAFLD) is a highly prevalent disease. Curcuminoids are anti-inflammatory agents with potential efficacy in NAFLD. We tested the efficacy of curcuminoids in patients with NAFLD in a clinical trial. Curcuminoids improved the severity of NAFLD according to ultrasound findings. Curcuminoids reduced serum TNF-α, MCP-1 and EGF levels in NAFLD patients. Abstract: Background: Nonalcoholic fatty liver diseases (NAFLD) is a highly prevalent disease that is closely associated with several cardiometabolic complications. The potential anti-inflammatory role of curcuminoids that have already been reported to reduce hepatic steatosis, in patients with NAFLD was explored in this study. Methods: This double-blind, randomized placebo-controlled trial was conducted for a period of 8 weeks in patients with NAFLD. Subjects (n = 55) were randomly allocated to receive either curcuminoids or placebo. The curcuminoids group received one capsule containing 500 mg curcuminoids (plus 5 mg piperine to increase intestinal absorption) per day for 8 weeks and the control group received matched placebo capsules for the same period. Liver ultrasonography was performed to assess the severity of hepatic steatosis at baseline and the study end. Serum levels of cytokines including interleukin-1α, interleukin-1β, interleukin-2, interleukin-4, interleukin-6, interleukin-8, interleukin-10, tumor necrosis factor-α, monocyte chemoattractant protein-1, interferon γ, vascular endothelial growth factor and epidermal growth factor were measured before and after the intervention. Results: The two groups were comparable in demographic features at baseline. The results showed that supplementation with curcuminoids could decrease weight compared to the placebo group (p = 0.016) in patients with NAFLD. Curcuminoids supplementation improved the severity of NAFLD according to the ultrasound results (p = 0.002). Moreover, serum concentrations of TNF-α (p = 0.024), MCP-1 (p = 0.008) and EGF (p = 0.0001) were improved by curcuminoids in NAFLD patients. Conclusions: The results of our study showed that curcumin supplementation can improve serum levels of inflammatory cytokines in subjects with NAFLD and this might be at least partly responsible for the anti-steatotic effects of curcuminoids.